Comparison of Antiepileptic Approaches in Treatment of Benzodiazepine Nonresponsive Status Epilepticus. (4th February 2016) - Bachhuber, Armin; Lasrich, Maike; Halmer, Ramona; Fassbender, Klaus; Walter, Silke
Summary: Aims: Status epilepticus and seizure clusters are common neurological emergencies. The purpose of this monocentric, retrospective cohort study was to comparatively assess different antiepileptic approaches in the treatment of status epilepticus and seizure clusters, which were nonresponsive to benzodiazepines. Methods: We reviewed medical records of 66 patients, who were treated for status epilepticus or seizure clusters in the Department of Neurology at the University of the Saarland between January 2007 and July 2012, and failed to respond to benzodiazepines with the equivalent dosage of at least 20 mg of diazepam. As endpoints, we analyzed both the effectiveness of lacosamide, levetiracetam, valproic acid, and phenytoin used as second‐ and third‐line therapy, and the Glasgow Outcome Scale at day 7. Results: Sixty‐one (92.4%) of the patients had status epilepticus, and 5 (7.6%) had seizure clusters. The compared drugs were equally effective in terminating seizures. There was also no significant difference in the Glasgow Outcome Scale ( P = 0.60) after 7 days. Conclusion: Our data support the use of the modern antiepileptic treatment strategies, such as levetiracetam, valproic acid, and lacosamide in the treatment of status epilepticus and seizure clusters.